Exponential Decay Metrics of Topical Tetracaine Hydrochloride Administration Describe Corneal Anesthesia Properties Mechanistically. Issue 3 (March 2017) - Ethington, Jason; Goldmeier, David; Gaynes, Bruce I.
Abstract : Purpose: To identify pharmacodynamic (PD) and pharmacokinetic (PK) metrics that aid in mechanistic understanding of dosage considerations for prolonged corneal anesthesia. Methods: A rabbit model using 0.5% tetracaine hydrochloride was used to induce corneal anesthesia in conjunction with Cochet–Bonnet anesthesiometry. Metrics were derived describing PD-PK parameters of the time-dependent domain of recovery in corneal sensitivity. Curve fitting used a 1-phase exponential dissociation paradigm assuming a 1-compartment PK model. Derivation of metrics including half-life and mean ligand residence time, tau (τ), was predicted by nonlinear regression. Bioavailability was determined by area under the curve of the dose–response relationship with varying drop volumes. Results: Maximal corneal anesthesia maintained a plateau with a recovery inflection at the approximate time of predicted corneal drug half-life. PDs of recovery of corneal anesthesia were consistent with a first-order drug elimination rate. The mean ligand residence time (tau, τ) was 41.7 minutes, and half-life was 28.89 minutes. The mean estimated corneal elimination rate constant (ke ) was 0.02402 minute −1 . Duration of corneal anesthesia ranged from 55 to 58 minutes. There was no difference in time domain PD area under the curve between drop volumes. Conclusions: Use of a small drop volume of a topical anesthetic (as low as 11 μL) is bioequivalent to conventional drop size and seems to optimize dosing regiments with a little effect on ke . Prolongation of corneal anesthesia may therefore be best achieved with administration of small drop volumes at time intervals corresponding to the half-life of drug decay from the corneal compartment.